Evaluation of the Implementation of Good Manufacturing Practice at the Slaughterhouse in Kolaka Regency - Asminaya, Nur Santy; Auza, Fuji Astuti; Bain, Ali; Nafiu, La Ode; Malesi, La; Zulkarnain, Deki; Tambing, Titin (Faculty of Agriculture, 2025)
Meat safety is a major component of food safety that impacts public health, so supervision and protection are needed. This study aims to analyze the level of Good Manufacturing Practices (GMP) implementation in providing safe, healthy, intact, and halal (ASUH) food in Kolaka Regency. The data collected focuses on the mechanism of beef production, the stages of receiving live cattle to becoming carcasses, and the evaluation of the level of compliance with the principles of GMP and halal control points (HCPs) in the beef production process. The method of determining respondents was non-probability sampling with incidental sampling techniques. The results showed that the implementation of GMP in general and the HCPs checklist at the Kolaka Regency slaughterhouse had values of 32.72 and 37.3, which are inadequate to meet GMP standards. The Kolaka Regency government must strive to build slaughterhouses with facilities and infrastructure that meet GMP standards. Halal butchers and slaughterhouse staff need regular training on GMP standard cutting techniques to produce ASUH meat. Supervision of cutting activities at the slaughterhouse also needs to be carried out. The conclusion is that it is necessary to improve and supervise all slaughterhouse activities so that GMP standard aspects can be met.